Enhancing elementary students’ creative thinking through creative problem solving-based learning materials: Evidence from Indonesia - S. Sahrul; Iis Siti Aisyah; Agus Tinus (Research and Development in Education (RaDEn), 2025)
Developing creative thinking is central to 21st-century elementary education, yet Indonesian primary classrooms often rely on teacher-centered materials. This study developed and implemented Creative Problem Solving (CPS) learning materials to strengthen grade-5 students’ creative thinking. A qualitative descriptive-analytic design was conducted at Muhammadiyah Elementary School Tanjung Selor (North Kalimantan) with one principal, three teachers, and 30 students; data included interviews, observations, document analysis, expert validation, and pre/post creative-thinking tests. Expert review indicated the module was feasible (overall mean = 4.30/5), with suggestions to simplify terms and enrich visuals. Classroom observations showed students engaged across CPS stages (problem orientation, fact finding, idea exploration, and solution presentation) and interacted more actively. Mean scores increased from 69.69 (pretest) to 85.04 (posttest), a gain of 15.35 points; students rated the module highly for fostering creativity (77.69%). CPS-based materials are feasible and effective for improving elementary students’ creative thinking, but scaling requires sustained teacher training, supportive leadership, and improved learning infrastructure.